Matching theory for wireless networks - Han, Zhu, 1974-; Gu, Yunan; Saad, Walid (Springer, 2017)
This book provides the fundamental knowledge of the classical matching theory problems. It builds up the bridge between the matching theory and the 5G wireless communication resource allocation problems. The potentials and challenges of implementing the semi-distributive matching theory framework into the wireless resource allocations are analyzed both theoretically and through implementation examples. Academics, researchers, engineers, and so on, who are interested in efficient distributive wireless resource allocation solutions, will find this book to be an exceptional resource.
Keywords: Matching theory.; Wireless communication systems.; elektronické knihy; electronic books